2006
DOI: 10.1103/physrevb.74.024417
|View full text |Cite
|
Sign up to set email alerts
|

Spin transport in an asymmetrical magnetic superlattice

Abstract: The electron spin transport in an asymmetrical magnetic superlattice ͑MSL͒, which is due to the periodic barriers with abnormal one in height, has been theoretically studied. The effects of the abnormal barrier in the MSL have been introduced by a defined asymmetry factor, which corresponds to the changeable height of the abnormal barrier. The results show that in the ballistic transport region, the spin-up electron transmission and conductance can be dramatically depressed by the enhancement of the asymmetry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 41 publications
(29 reference statements)
1
29
0
Order By: Relevance
“…One important characteristic of phononic crystals is the existence of the absolute band gaps, which represent frequency regions where propagating elastic waves do not exist [3][4][5][6][7]. The study of phononic crystals has shown that gaps can exist in a lot of systems of any dimension (one-dimensional (1D), two-dimensional (2D) and three-dimensional (3D)) systems.…”
Section: Introductionmentioning
confidence: 99%
“…One important characteristic of phononic crystals is the existence of the absolute band gaps, which represent frequency regions where propagating elastic waves do not exist [3][4][5][6][7]. The study of phononic crystals has shown that gaps can exist in a lot of systems of any dimension (one-dimensional (1D), two-dimensional (2D) and three-dimensional (3D)) systems.…”
Section: Introductionmentioning
confidence: 99%
“…The magnetic field is created by the deposition, on top of the heterostructure, of two parallel metallic ferromagnetic strips. This has been investigated in detail by several authors [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 98%
“…The expected advantages of spintronics devices are nonvolatility, higher integration densities, lower power operation and higher switching speeds. Extensive efforts have been devoted to exploring the electron-spin polarization properties in a wide variety of structures [2][3][4][5][6][7][8][9][10][11][12][13][14], such as magnetic dots [5,6], superlattices [7][8][9][10][11], wires [12,13], and transverse steps [14], which could be realized experimentally in non-planar two-dimensional electron gas (2DEG) [15,16], or by patterning ferromagnetic and superconducting materials [17]. In fact, the electron spin-dependent properties in artificial nanostructures have become one of the today's leading subjects in the physics of electronic devices.…”
Section: Introductionmentioning
confidence: 99%